Learning to See in Western Amazonia: How Does Form Reveal Relation?. Issue 2 (1st June 2019) - Lagrou, Els
Abstract : Through the study of form, we explore how relations constitute persons for the Huni Kuin of Western Amazonia. Shamanistic song, and the role in it of patterned design, reveals a specific aesthetics that emphasizes processes of becoming, transformation, and figure/ground reversal. Since bodily substances and actions of others affect the 'thinking body', well-being depends on making visible the relational network that exists inside and outside one's embodied self. An aesthetic battlefield unfolds where the doubles of ingested substances invert the predatory relation and come to envelop the 'eye soul' of the one who ingested them with their design and ornaments. This setting allows us to address the fractal quality of personhood and the permanent disequilibrium between symmetrical and asymmetrical relations in Amazonia.